Regulando el fin de la esclavitud: Diálogos, innovaciones y disputas jurídicas en las nuevas repúblicas sudamericanas 1810-1830 - Candioti, Magdalena (2015)
The main purpose of this work is to elucidate the moment of strong experimentation and legal innovation, regarding slavery‟s regulation and its end, that opened up in some of the Hispanic American new republics between 1810 and 1830. The article reconstructs some of the legal tools and models of abolition that were thought and discussed by elites and used, and sometimes debated, by subaltern subjects that were part of these legal spaces in process of redefinition and construction. The legal tools discussed were the “free womb” laws, the patronage on freed blacks, the idea of “free soil”, the abolitions of the slave trade, and immediate abolition of slavery. The article reflects on the logic of these measures as well as on the explicit or implicit borrowings among elites that were creating a new way of relationship with the populations of African descent, the regulation of their work and its possibilities to access to citizenship in the new legal and political orders. At the same time, it argues that the letter of the law did not involve immediate changes in the condition of the enslaved since they had to fight over its interpretation in order to really acquire rights and improve their lives.